CONCEPT OF RUDRA PASHUPATI AMONG BRAHMINS: ब्राह्मणों में रूद्र पशुपति की संकल्पना - Mishra, Satendra (International Journal of Research -GRANTHAALAYAH, 2021)
English : Seven names of Rudra are also mentioned in the Atharvaveda, which appear to be the principal names of Shiva in the later Shaiva sects. These seven names are - bhava, sharava, pashupati, avid, rudra, mahadev, ishaan. Although it is common that all these Namdhari deities are depicted as different deities. Bhava and Shiva are said to be the deity ruling over animals and humans. No human or deity can escape from their arrows. He is invited to kill Yatu Dhanu (demon) and other evil spirits. The body has been called the arrowhead and Bhava has been called the king. A desire has also been expressed to take the deadly poisons of his arrows to another place. The omnipresence of Rudra has also been shown, while he has been described as eminent in fire, in waters, in herbs and other plants, and is said to have created all creatures. It is also known that the same mantra was used for Rudra in Atharvasiras Upanishad and Sweteshvatara Upanishad. It has also been said to be the Bhootpati and Pashupati of Bhava and Sharva. Five types of animals ie cows, blacks, humans and sheep and azas are mentioned under the authority of Pashupati. Rudra is also depicted as Dikpal. Ugra is said to be the lord of the four directions and the sky, earth and space. A Sukta prayed that Rudra should not spread diseases, poisons and heavenly fire. Bhava is called Ish and Rajan. It is said in one place that Bhava, Sharva and Rudra who is Pashupati are always (Sadasiva) welfare. It has also been said that the Gods made the Bhava with arrows the protector of the vratas and the lord of the east direction. Made the body the lord of the south direction. Made Rudra the lord of the earth. Made Mahadev the lord of the divine world. Made Ishan into space. Hindi : अथर्ववेद में रूद्र के सात नामों का भी उल्लेख किया गया है, जो उत्तरकालीन शैव सम्प्रदायों में शिव के प्रधान नामों के रूप में आते हैं। ये सात नाम हैं - भव, शर्व, पशुपति, उग्र, रूद्र, महादेव, ईशान। यद्यिपि यह सम्य है कि इन सभी नामधारी देवताओं को विभिन्न देवताओं के रूप में चित्रित कियाग गया है। भव और शर्व को पशुओं और मानवों पर शासन करने वाला देवता बताया गया है। उनके बाणों से देवता अथवा कोई भी मनुष्य नहीं बच सकता है। उन्हें यातु धानु (राक्षस) तथा अन्य बुरी आत्माओं को मारने के लिए आमन्त्रित किया गया है। शर्व को बाण चलाने वाला कहा गया है और भव को राजा कहा गया है। इस बात की भी इच्छा प्रकट की गई है कि वे अपने बाणों के घातक विषों को दूसरे स्थान पर ले जाएँ।67 रूद्र ने इन देवताओं को आत्मसात् कर लिया तथापि रूद्र के यही आठ देवरूप पौराणिक शिवके आठ रूपों में समा सकते हैं। रूद्र की सर्वव्यापकता को भी दिखाया गया है, जबकि उसे अग्नि में, जलों में, जड़ी-बूटियों तथा अन्य पौधों में प्रतिष्ट बताया गया है और कहा है कि सभी जीवों को इन्होंने ही बनाया है। यह भी द्रष्टव्य है कि यही मन्त्र अथर्वसिरस उपनिषद और श्वेताश्वेतर उपनिषद् में रूद्र के लिए प्रयुक्त हुआ। भव और शर्व का भूतपति और पशुपति भी कहा गया है। पाँच प्रकार के पशुओं अर्थात् गायों, अश्वों, मनुष्यों और भेड़ों तथा अजों को पशुपति के अधिकार में बताया गया है। रूद्र को दिक्पाल के रूप में भी चित्रित किया गया है। उग्र को चारों दिशाओं तथा आकाश, पृथ्वी एवं अंतरिक्ष का स्वामी बताया गया है। एक सूक्त में प्रार्थना की गई है कि रूद्र व्याधियों, विषों और स्वर्गीय अग्नि को न फैलाए। भव को ईश तथा राजन कहा गया है। एक स्थान में कहा गया है कि भव, शर्व और रूद्र जो पशुपति है, सदैव (सदाशिव) कल्याणकारी हैं। यह भी कहा गया है कि देवताओं ने बाण चलाने वाले भव को व्रात्यों का रक्षक बनाया और पूर्व दिशा का स्वामी बनाया। शर्व को दक्षिण दिशा का स्वामी बनाया। रूद्र को पृथ्वी लोक का स्वामी बनाया। महादेव को दिव्यलोक का स्वामी बनाया। ईशान को अन्तरिक्ष बनाया।